Welded structure and finishing method for welded structure
By ensuring a chromium content of at least 1.5 times that of the base metal and effectively removing oxide scale, the welded structure enhances corrosion resistance and reliability in duplex stainless steel welds, addressing the chromium-deficient layer issue and localized corrosion in high chloride environments.
Patent Information
- Application Number
- JP2021098954
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-14
- Publication Date
- 2025-01-06
- Estimated Expiration
- 2041-06-14
AI Technical Summary
Existing methods for welding duplex stainless steel fail to adequately remove oxide scale, leading to chromium-deficient layers that reduce corrosion resistance, particularly in environments with high chloride concentrations, and the process of removing oxide scale can introduce localized corrosion starting points.
A welded structure where the surface of the weld metal has a chromium content at least 1.5 times that of the base metal, with sufficient removal of oxide scale using methods like pickling, electrolytic treatment, or heat treatment to ensure a chemical composition with enhanced corrosion resistance.
The method improves the corrosion resistance of duplex stainless steel welds, reducing susceptibility to localized corrosion and ensuring high reliability in corrosive environments.
Smart Images

Figure 0007608278000003 
Figure 0007608278000004 
Figure 0007608278000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a welded structure having high corrosion resistance in which duplex stainless steel is welded, and to a finishing method for a welded structure for obtaining the same. [Background technology]
[0002] Duplex stainless steel is known as a stainless steel with excellent strength, toughness, and corrosion resistance. Duplex stainless steel is a material in which the ferrite phase and the austenite phase are formed in approximately equal ratios, and has excellent pitting corrosion resistance in the presence of moisture. For this reason, it is used as a material for tanks and piping in water treatment plants and chemical plants, as well as oil well tubular goods and oil transmission pipes in oil and natural gas mining plants.
[0003] Duplex stainless steel has low susceptibility to hot and cold cracking and good weldability, so it is often joined by welding. Nitrogen is added to duplex stainless steel to improve strength, corrosion resistance, and save expensive Ni. Nitrogen added to the base metal precipitates chromium nitride in the heat-affected zone formed by welding. As a result, a chromium-deficient layer is formed in the weld, which poses a problem in the corrosion resistance of the weld.
[0004] It is known that an oxide scale forms on the surface of a welded part of stainless steel. The oxide scale is mainly composed of oxides of Fe, not Cr. When the oxide scale forms, the surface of the weld shows so-called weld burn, discoloring to brown or purple, impairing the appearance, and it is known that the corrosion resistance of the weld is reduced. It is said that the weld is particularly susceptible to localized corrosion such as pitting corrosion and crevice corrosion because a gap is formed between the weld and the base material and a chromium-depleted layer is formed.
[0005] TIG welding is generally used as a method for welding duplex stainless steel. In TIG welding, a shielding gas such as argon gas is used to block oxygen and nitrogen. However, even when a shielding gas is used, it is difficult to completely prevent the formation of oxide scale on the surface of the weld.
[0006] Duplex stainless steels are also used in environments with high chloride concentrations. Chlorine-based disinfectants such as hypochlorous acid are used in water treatment plants, such as seawater desalination plants. Chlorine-based disinfectants have a high redox potential, which increases the potential of the welds of duplex stainless steels. This increase in potential increases the susceptibility to localized corrosion, so there is a demand for further improvement in corrosion resistance.
[0007] Patent Document 1 describes a duplex stainless steel that has excellent corrosion resistance in a fluid environment containing an oxidizing substance. Patent Document 1 specifies the chemical composition of the welded material itself in order to increase the corrosion resistance of the heat-affected zone.
[0008] Patent Document 2 describes a pickling agent used for pickling duplex stainless steel with excellent corrosion resistance. The pickling agent in Patent Document 2 contains nitric acid, hydrofluoric acid, an inorganic acid other than hydrofluoric nitric acid, an organic acid, a magnesium compound, and a surfactant. This pickling agent is said to be used for welded parts of duplex stainless steel.
[0009] Patent Document 3 does not describe duplex stainless steel, but describes a method for improving the corrosion resistance of a welded portion of a general stainless steel. -4 ~10 -2 The weld is heated at 400-600°C for at least one hour in a vacuum atmosphere of Torr to increase the Cr ratio on the weld surface. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2018-168461 A [Patent Document 2] JP 2007-297697 A [Patent Document 3] Japanese Patent Application Publication No. 9-13124 Summary of the Invention [Problem to be solved by the invention]
[0011] In order to improve the corrosion resistance of the welded parts of duplex stainless steels, it is important to remove the oxide scale formed on the welded parts and to make the welded parts have a chemical composition with high corrosion resistance. However, even if the treatment for removing the oxide scale is performed, the oxide scale may not be sufficiently removed, and the susceptibility to localized corrosion may not be sufficiently reduced. In addition, the treatment for removing the oxide scale itself may be a cause of the formation of starting points for localized corrosion in the base material.
[0012] Patent Documents 1 to 3 describe techniques for improving the corrosion resistance of stainless steel and its welded parts. However, Patent Documents 1 to 3 do not disclose the chemical composition of the weld metal of the welded parts. Patent Document 3 discloses that a chromium-deficient layer in an oxide film deteriorates corrosion resistance, so a method of polishing and pickling the welded parts is effective. However, it does not disclose the extent to which the oxide scale should be removed, or the possibility that the process of removing the oxide scale itself may cause corrosion.
[0013] Therefore, an object of the present invention is to provide a welded structure in which the corrosion resistance of a welded portion of a duplex stainless steel is improved and the reliability of a product in which a welded portion is formed is increased, and a finishing method for a welded structure to obtain the same. [Means for solving the problem]
[0014] In order to solve the above problems, the present invention provides a welded structure in which duplex stainless steel is welded, the welded structure having a welded portion in which a base material formed of duplex stainless steel is joined via a weld metal, and the welded structure has a welded portion in which a base material formed of duplex stainless steel is joined via a weld metal, the welded structure having a welded portion in which a base material formed of duplex stainless steel is joined via a weld metal, the welded structure having a welded portion in which a base material formed of duplex stainless steel is joined via a weld metal, the welded structure having a welded portion in which a base material formed of duplex stainless steel is joined via a weld metal, the welded portion ... Measured by X-ray photoelectron spectroscopy The Cr content at the surface of the weld metal is Cr content in This is more than 1.5 times the amount.
[0015] The method for finishing a welded structure according to the present invention is a method for finishing a welded structure in which duplex stainless steel is welded, and includes a step of removing oxide scale from a welded portion in which a base material formed of duplex stainless steel is joined via a weld metal, and the step of removing the oxide scale includes, in mass % excluding oxygen and carbon, Measured by X-ray photoelectron spectroscopy The Cr content at the surface of the weld metal is Cr content in The surface of the weld metal is 1.5 times or more Fe included This is the process of removing oxide scale. Effect of the Invention
[0016] According to the present invention, it is possible to provide a welded structure in which the corrosion resistance of a weld of a duplex stainless steel is improved and the reliability of a product in which a weld is formed is increased, and a method of finishing a welded structure for obtaining the same. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a diagram showing the configuration of an apparatus for performing electrolysis by a direct current method. [Diagram 2] FIG. 1 is a diagram showing the configuration of an apparatus for performing electrolysis by an indirect current method. [Diagram 3] 1 is an image showing the appearance of a welded material made by welding two pieces of duplex stainless steel together before descaling. [Figure 4] 1 is an image showing the appearance of a welded material in which two pieces of duplex stainless steel are welded together after descaling. [Figure 5A] 1A to 1C are diagrams showing a method for providing a gap to a welded material. [Figure 5B] 1A to 1C are diagrams showing a method for providing a gap to a welded material. [Figure 5C] 1A to 1C are diagrams showing a method for providing a gap to a welded material. [Figure 5D] 1A to 1C are diagrams showing a method for providing a gap to a welded material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, a welded structure and a method for finishing a welded structure according to an embodiment of the present invention will be described with reference to the drawings. In the following drawings, common configurations are given the same reference numerals and duplicated descriptions will be omitted.
[0019] The welded structure according to this embodiment is a structure in which duplex stainless steel is welded. This welded structure is formed by welding together a base material, which is a material to be welded and made of duplex stainless steel, and a mating material, which is a material to be welded. The welded structure has a weld between the base material and the mating material, in which the base material is joined to the mating material via a weld metal.
[0020] The welded parts of welded structures are composed of the weld metal and the heat-affected zone (HAZ). The weld metal is a region formed by integrating the base material, mating material, and deposited metal, and is formed when the base material, mating material, and the filler metal used in welding melt and then solidify. The heat-affected zone is a region that is not melted but has been altered by heat, and is formed near the boundary between the base material adjacent to the weld metal and the mating material.
[0021] As the base metal, which is the material to be welded, there can be used duplex stainless steels with an appropriate pitting corrosion resistance index, such as super duplex stainless steels such as SUS327, general-purpose duplex stainless steels such as SUS329, lean duplex stainless steels such as SUS321 and SUS323, etc. The corrosion resistance index of the duplex stainless steels and the fraction of the austenite phase and ferrite phase are not particularly limited.
[0022] The mating material to be welded may be any suitable weldable material, such as duplex stainless steels, such as super duplex stainless steels, general-purpose duplex stainless steels, lean duplex stainless steels, etc., austenitic stainless steels, ferritic stainless steels, carbon steels, nickel-based alloys, etc. The preferred mating material is duplex stainless steel.
[0023] In the welded structure according to this embodiment, the amount of a predetermined element related to corrosion resistance is limited to a predetermined range on the surface of the weld metal. When the element amount and chemical composition of the surface of the weld metal are measured, the amount of the predetermined element on the surface of the weld metal is limited to a predetermined range, which ensures that the oxide scale on the surface of the weld is sufficiently removed and that the chemical composition of the surface layer of the weld is excellent in corrosion resistance. This improves the corrosion resistance of the weld, particularly the crevice corrosion resistance.
[0024] The amount of elements related to corrosion resistance on the surface of the weld metal is measured after treatment to remove the oxide scale formed on the surface of the weld. Oxide scale is a product of oxide film and the like that is mainly composed of oxides of Fe, not Cr. Elements related to corrosion resistance include chromium (Cr), nickel (Ni), and molybdenum (Mo), which contribute to improving corrosion resistance, and manganese (Mn), which is an indicator of a decrease in corrosion resistance.
[0025] The elemental amounts and chemical composition on the surface of the weld metal can be measured by X-ray photoelectron spectroscopy (XPS) analysis. The measurement position is not particularly limited as long as it is on the surface of the weld metal exposed to the outside of the welded structure. For example, the measurement can be performed by irradiating the center of the surface of the weld metal with X-rays. Note that an oxide film mainly composed of Cr oxide may be formed on the surface of the weld metal.
[0026] XPS analysis provides qualitative and quantitative information up to a depth of several tens of nanometers from the measurement position. Therefore, if no oxide scale remains on the surface of the weld metal after treatment to remove the oxide scale, measurement results for the surface layer of the weld metal are obtained. On the other hand, if oxide scale remains on the surface of the weld metal, measurement results for both the oxide scale and the surface layer of the weld metal are obtained.
[0027] In this way, by measuring the amount of elements on the surface of the weld metal after the treatment to remove the oxide scale, the corrosion resistance of the weld can be evaluated more accurately under conditions closer to those during practical use. The measurement results taken into account the extent to which the oxide scale has been removed and the effects of the treatment to remove the oxide scale itself. Therefore, by selecting appropriate chemical compositions for the base metal, mating metal, and filler metal, and by selecting appropriate conditions for the treatment to remove the oxide scale, the corrosion resistance of the weld can be improved compared to conventional methods.
[0028] The Cr amount at the surface of the weld metal, in mass % excluding oxygen and carbon, is preferably 1.5 times or more, more preferably 1.6 times or more, even more preferably 1.7 times or more, and even more preferably 1.8 times or more, of the Cr amount in the base metal formed of duplex stainless steel.
[0029] Such a Cr amount means that a large amount of Cr was detected by the measurement, and that no thick oxide scale was measured. In other words, the oxide scale on the surface of the weld metal was sufficiently removed. Also, the surface layer of the weld metal was not deficient in Cr. Therefore, Cr has the effect of forming a passive film and improving corrosion resistance. Also, the state in which the oxide scale was sufficiently removed ensures high local corrosion resistance.
[0030] The Mn content on the surface of the weld metal, in terms of mass % excluding oxygen and carbon, is preferably equal to or less than the Mn content in the base metal formed of duplex stainless steel.
[0031] Such an amount of Mn means that the amount of Mn detected by the measurement is small, and that no thick oxide scale is measured. In other words, the oxide scale on the surface of the weld metal has been sufficiently removed. This is because Mn is concentrated in the oxide scale mainly composed of Fe oxides, and dissolves from the surface layer of the weld metal when pickling or the like is performed. Therefore, high local corrosion resistance is ensured by the state in which the oxide scale is sufficiently removed.
[0032] The Ni content in the surface of the weld metal, in mass % excluding oxygen and carbon, is preferably 0.4 times or more, and more preferably 0.5 times or more, the Ni content in the base metal made of duplex stainless steel, and the Mo content in the surface of the weld metal is preferably 1.5 times or more, and more preferably 1.6 times or more, the Mo content in the base metal made of duplex stainless steel.
[0033] Such amounts of Ni and Mo mean that a large amount of Ni and Mo was detected by the measurement, and no thick oxide scale was measured. In other words, the oxide scale on the surface of the weld metal has been sufficiently removed. Also, the surface layer of the weld metal is not deficient in Ni or Mo. Therefore, Ni has the effect of suppressing the progress of local corrosion, and Mo has the effect of strengthening the passive film and improving corrosion resistance. Also, the state in which the oxide scale has been sufficiently removed ensures high local corrosion resistance.
[0034] The amount of each element on the surface of the weld metal is limited by the mass fraction per 100 mass% of the total of other elements excluding oxygen and carbon contained in the weld metal. Oxygen is mainly present in oxide scale and in oxide films mainly composed of Cr oxides, but it can be mixed into the surface layer of the weld metal from the oxide scale or the atmosphere. Carbon can be mixed in from vacuum pump oil, etc., when the process of removing oxide scale is performed under reduced pressure conditions.
[0035] In the welded structure according to the present embodiment, it is preferable that at least the Cr content is limited on the surface of the weld metal, more preferably the Cr content and Mo content are limited, even more preferably the Cr content, Mo content and Ni content are limited, and even more preferably the Cr content, Mo content, Ni content and Mn content are limited. This is because Cr and Mo are related to basic corrosion resistance, whereas Ni is secondarily related to the progress of localized corrosion. This is because Mn is related as an indicator of the decrease in localized corrosion resistance due to oxide scale.
[0036] The application of the welded structure according to the present embodiment is not particularly limited. The welded structure according to the present embodiment can be used, for example, in water treatment systems, seawater desalination systems, seawater concentration systems, radioactively contaminated water treatment systems, radioactive waste liquid treatment systems, chemical plants, oil mining plants, natural gas mining plants, etc. The welded structure according to the present embodiment can be preferably used for pipes in these facilities, joints of piping equipment such as pumps, valves, sensors, and tanks, and particularly for liquid-contacting parts with high water or chloride concentrations.
[0037] In such a welded structure, the amount of elements related to corrosion resistance on the surface of the weld metal measured by XPS analysis is limited to a predetermined range, so that the oxide scale is sufficiently removed from the welded portion, and the entire welded metal, including the surface layer, has a chemical composition with excellent corrosion resistance. This reduces the susceptibility to local corrosion such as pitting corrosion and crevice corrosion caused by the oxide scale, and improves the corrosion resistance of the welded metal itself. This improves the corrosion resistance of the welded portion, thereby increasing the reliability of the welded structure product having the welded portion.
[0038] In particular, welded structures are subject to high chloride concentrations such as seawater, which has a chloride concentration of 2×10 4Even in a corrosive environment exceeding ppm, if oxide scale is properly removed, it is possible to prevent localized corrosion from occurring. In welds, the austenite phase does not grow easily and chromium nitrides are likely to precipitate, causing chromium-deficient layers, but because the Cr content in the surface layer of the weld metal can be optimized, it is possible to suppress the occurrence and progression of localized corrosion in welds for a long period of time.
[0039] Next, a method for finishing the welded structure to obtain the above-mentioned welded structure will be described.
[0040] The above-mentioned welded structure, in which the amount of elements related to corrosion resistance on the surface of the weld metal is limited to a predetermined range, can be obtained by a method including the steps of welding a base material, which is a material to be welded and made of duplex stainless steel, and a mating material, which is a material to be welded, together using a filler metal, and removing oxide scale from the weld where the base material, which is made of duplex stainless steel, is joined via the weld metal.
[0041] As the welding method, an appropriate welding method such as groove welding, fillet welding, seam welding, etc. can be used. As the material to be welded, an appropriate material such as plate material, tube material, bar material, formed material, etc. can be welded. As the welding method, any welding method such as TIG welding, MIG welding, MAG welding, shielded metal arc welding, laser welding, etc. can be used. As the welding method, either single layer welding or laminate welding can be used. There are no particular limitations on the groove shape, laminate pass conditions, heat input conditions, etc.
[0042] When welding to form a welded structure, an appropriate filler metal can be used depending on the material to be welded. As the filler metal, a flux-cored welding material or a flux-free welding material can be used depending on the welding method. By using a filler metal with an appropriate chemical composition, the amount of elements related to the corrosion resistance of the weld metal can be adjusted relative to the base metal.
[0043] It is preferable to use a filler metal that is richer in the amount of elements related to corrosion resistance than the base metal. In other words, it is preferable to use a filler metal with a chemical composition that results in a higher amount of Cr, Mo, Ni, etc. than the base metal when the base metal and filler metal are integrated. By using such a filler metal, the amount of elements related to corrosion resistance in the weld metal can be adjusted, thereby increasing the corrosion resistance of the welded part.
[0044] As the filler metal, a material having a Cr content of 1.5 times or more than that of the base material in mass % excluding oxygen and carbon is more preferable. A material having a Cr content of 1.5 times or more than that of the base material and a Mo content of 1.5 times or more than that of the base material is even more preferable. A material having a Cr content of 1.5 times or more than that of the base material, a Mo content of 1.5 times or more than that of the base material and a Ni content of 0.4 times or more than that of the base material is even more preferable.
[0045] In the process of removing the oxide scale from the welded portion, the oxide scale on the surface of the welded metal is removed so that the Cr content on the surface of the welded metal is 1.5 times or more that of the base material formed of duplex stainless steel. If the oxide scale mainly composed of Fe oxides is sufficiently removed, the corrosion resistance of the welded portion is improved, and a welded structure having a welded portion with high local corrosion resistance can be completed.
[0046] In the process of removing the oxide scale from the weld zone, it is preferable to remove the oxide scale on the surface of the weld metal so that the Cr content on the surface of the weld metal is 1.5 times or more that of the base metal and the Mn content on the surface of the weld metal is less than that of the base metal, the Ni content on the surface of the weld metal is 0.4 times or more that of the base metal, and the Mo content on the surface of the weld metal is 1.5 times or more that of the base metal.
[0047] Methods for removing oxide scale from the surface of the weld metal include (1) pickling the surface of the weld metal, (2) electrolytically treating the surface of the weld metal in a neutral salt solution, and (3) reducing heat treatment of the surface of the weld metal.
[0048] (1) The method of pickling the surface of the weld metal can be carried out by bringing the welded part into contact with an acid. After the welded part of the welded structure is brought into contact with an acid for pickling, the welded part is washed with water and dried. The pickling may be any of a process of immersing the welded part in an acid solution, a process of spraying the acid solution onto the welded part with a spray or the like, a process of applying the acid solution to the welded part with a brush or the like, and the like.
[0049] The acid may be an inorganic acid such as nitric acid, sulfuric acid, or hydrofluoric acid, or a mixed acid of at least one of these. The mixed acid may be nitric acid or hydrofluoric acid, which is a mixture of nitric acid and hydrofluoric acid. A pickling promoter, a pickling inhibitor, or the like may be added to the acid solution. It is preferable not to use hydrochloric acid at a high concentration, because hydrochloric acid easily acts on the surface layer of the weld metal even if there is oxide scale.
[0050] The concentration of nitric acid is preferably 2% to 50% in terms of appropriate pickling speed. The concentration of sulfuric acid is preferably 2% to 50% in terms of appropriate pickling speed. The concentrations of hydrofluoric nitric acid are preferably, for example, nitric acid 2% to 50% and hydrofluoric acid 0.2% to 10%.
[0051] The temperature of the acid is preferably 50° C. or higher and 80° C. or lower. When the temperature is 50° C. or higher, oxide scale can be sufficiently removed even in a relatively short treatment time. When the temperature is 80° C. or lower, uneven treatment and roughness of the base surface due to a high pickling speed can be suppressed.
[0052] The time for pickling treatment depends on the type of acid, the temperature of the acid solution, etc., but is preferably 3 minutes or more and 10 minutes or less. If the time for pickling treatment is too short, the oxide scale cannot be sufficiently removed, and uneven treatment is likely to occur. On the other hand, if the time for pickling treatment is too long, the surface of the base is likely to become rough.
[0053] The amount of elements related to the corrosion resistance on the surface of the weld metal is affected by the degree of removal of oxide scale and the elution of elements in the surface layer of the weld metal, and therefore can be adjusted to an appropriate range by the type of acid, the temperature of the acid, the pickling treatment time, etc.
[0054] (2) The method of electrolytically treating the surface of the weld metal in a solution of neutral salt can be carried out by immersing the weld in an electrolyte of neutral salt and passing an electric current through the weld to cause an electrochemical reaction. The weld of the welded structure is immersed in an electrolyte of neutral salt to perform electrolytic polishing, and then washed with water and dried.
[0055] The electrolyte can be an aqueous solution containing a neutral salt of an inorganic acid or an organic acid. The neutral salt can be sodium sulfate, sodium nitrate, ammonium sulfate, or a mixture of at least one of these. The use of a neutral salt can suppress the elution of elements from the surface layer of the weld metal compared to electrolytic polishing using an acid solution. In addition, the amount of waste liquid generated can be reduced. The use of sodium nitrate can efficiently form an oxide film mainly composed of Cr oxide on the surface of the weld while removing oxide scale.
[0056] The concentration of sodium sulfate is preferably 10% or more and 30% or less from the viewpoint of maintaining the current density and potential, etc. The concentration of sodium nitrate is preferably 10% or more and 30% or less from the viewpoint of maintaining the current density and potential, etc. The concentration of ammonium sulfate is preferably 10% or more and 30% or less from the viewpoint of maintaining the current density and potential, etc.
[0057] The current density of the material to be treated in electrolytic treatment is 2A / dm 2 More than 20A / dm 2 It is preferable that the current density is 2 A / dm or less. 2 If the current density is less than 20 A / dm, it is difficult to sufficiently remove the oxide scale. 2 If the current density exceeds 2A / dm, discoloration of the treated material occurs, and Cr, Mo, etc., which improve corrosion resistance, are excessively dissolved, resulting in a chemical composition of the surface layer of the weld metal with poor corrosion resistance. 2 More than 20A / dm2 If the thickness is not more than this, it is possible to appropriately improve the corrosion resistance of the base while removing oxide scale.
[0058] The time for which the current is applied during electrolytic treatment is preferably 3 minutes or more and 10 minutes or less, depending on the current density, etc. If the time for which the current is applied is too short, the oxide scale cannot be sufficiently removed, and unevenness in the treatment is likely to occur. On the other hand, if the time for which the current is applied is too long, the surface of the base is likely to become rough.
[0059] The amount of elements related to the corrosion resistance on the surface of the weld metal is affected by the degree of removal of oxide scale, which is mainly composed of Fe oxides, and the dissolution of elements in the surface layer of the weld metal, so it can be adjusted by changing the current density, the time of electrolytic treatment, etc.
[0060] Fig. 1 is a diagram showing the configuration of an apparatus for performing electrolysis by a direct current method, and Fig. 2 is a diagram showing the configuration of an apparatus for performing electrolysis by an indirect current method. 1 and 2, reference numeral 1 denotes an electrolytic cell, reference numeral 2 denotes an electrolyte, reference numeral 3 denotes an electrode, reference numeral 4 denotes a welded structure which is a material to be treated, and reference numeral 5 denotes a DC power source.
[0061] As shown in Figures 1 and 2, the method of electrolytically treating the surface of the weld metal can be either a direct current method in which a current is passed directly to the weld, or an indirect current method in which a current is passed indirectly to the weld.
[0062] In the direct current method shown in FIG. 1, a welded structure 4, which is the material to be treated, and an electrode 3, which serves as a counter electrode, are placed in an electrolytic cell 1. The welded structure 4 is electrically connected to the positive electrode of a DC power source 5. The electrode 3 is electrically connected to the negative electrode of the DC power source 5. The electrode 3 can be made of carbon, tantalum, or the like. An electrolyte 2 having a neutral salt dissolved therein is placed in the electrolytic cell 1, and the welded structure 4 and the electrode 3 are immersed in the electrolyte 2.
[0063] In the direct current method, the welded structure 4 is used as the anode and the electrode 3 is used as the cathode, and a direct current is applied from a direct current power source 5. The current causes an electrochemical reaction in the oxide scale formed on the surface of the weld of the welded structure 4, thereby removing the oxide scale.
[0064] In the indirect current method shown in Fig. 2, a welded structure 4, which is the material to be treated, and at least a pair of electrodes 3 are placed in an electrolytic cell 1. A plurality of electrodes 3 may be arranged in tandem or the like. Each electrode 3 is electrically connected to a positive electrode or a negative electrode of a DC power source 5. An electrolyte 2 having a neutral salt dissolved therein is placed in the electrolytic cell 1, and the welded structure 4 and the electrodes 3 are immersed in the electrolyte 2.
[0065] In the indirect current method, a direct current is applied from a direct current power source 5 between electrodes 3 adjacent to a welded structure 4. The application of current causes polarization in the welded structure 4, which induces an electrochemical reaction in the oxide scale, mainly composed of Fe oxides, formed on the surface of the weld of the welded structure 4, thereby removing the oxide scale. Since the electrolysis is performed in a neutral salt solution, the anodic reaction prevails over the cathodic reaction on the surface of the welded structure 4.
[0066] The direct current method shown in Fig. 1 enables electrolytic processing with excellent power efficiency. On the other hand, the indirect current method shown in Fig. 2 is inferior in power efficiency but can reduce uneven processing. In Fig. 2, the welded structure 4, which is the material to be processed, is fixed to the electrode 3, but it can also be moved relative to the electrode 3. The electrode 3 can be provided in a movable scanning manner relative to the welded structure 4, or the welded structure 4 can be transported relative to the electrode 3.
[0067] (3) The method of reducing heat treating the surface of the weld metal can be performed by heat treating the weld at high temperature in a reduced pressure atmosphere.
[0068] The heat treatment temperature is preferably 400° C. or higher. The heat treatment temperature is preferably 600° C. or lower. The heat treatment time is preferably 1 hour or longer. The heat treatment time depends on the heat treatment temperature, pressure conditions, etc., but is preferably 3 hours or shorter. The pressure conditions for the heat treatment are as follows: 10 -2 Torr or less is preferable. 10 -2 Heat treatment at 400°C or higher for one hour or more in a reduced pressure atmosphere of less than Torr can sufficiently remove oxide scale mainly composed of Fe oxides.
[0069] The amount of elements related to the corrosion resistance on the surface of the weld metal is affected by the degree of removal of oxide scale mainly composed of Fe oxides, and can be adjusted by changing the heat treatment temperature, heat treatment time, heat treatment pressure conditions, etc. Under low vacuum conditions, it is preferable to perform heat treatment at a low temperature or for a short time. On the other hand, under high vacuum conditions, heat treatment at a high temperature or for a short time can be performed.
[0070] According to this method for finishing a welded structure, it is possible to obtain a welded structure in which the amount of elements related to corrosion resistance at the surface of the weld metal measured by XPS analysis is limited to a predetermined range. The welded part of the welded structure is in a state in which oxide scale mainly composed of oxides of Fe, not Cr, has been sufficiently removed, and the entire welded metal, including the surface layer, has a chemical composition with excellent corrosion resistance. Therefore, the susceptibility to local corrosion such as pitting corrosion and crevice corrosion caused by the oxide scale is reduced. In addition, the corrosion resistance of the welded metal itself is ensured. Therefore, the corrosion resistance of the welded part can be improved, and the reliability of the welded structure product having the welded part can be increased. EXAMPLES
[0071] The present invention will be specifically described below with reference to examples, but the technical scope of the present invention is not limited to these examples.
[0072] The welds of duplex stainless steels welded together were treated to remove oxide scale from the weld metal surface, and the relationship between the chemical composition of the weld metal surface and crevice corrosion resistance was evaluated.
[0073] The materials to be welded were either S32750, a super duplex stainless steel, or S32205, a general-purpose duplex stainless steel. Plates made of the same type of duplex stainless steel were butt-welded together by TIG welding using a duplex stainless steel filler metal.
[0074] The filler metal used was a duplex stainless steel welding wire, which is richer in Cr, Mo, and Ni than the base metal made of duplex stainless steel and contains Mn, Fe, SiO2-based flux, etc. A mixture of argon and nitrogen gas was used as the shielding gas during welding.
[0075] Figure 3 is an image showing the appearance of a welded material made by welding two duplex stainless steels together before descaling, and Figure 4 is an image showing the appearance of a welded material made by welding two duplex stainless steels together after descaling. Figures 3 and 4 show welded material obtained by butt-welding two plates of S32750, a super duplex stainless steel. Figure 3 shows the condition before descaling treatment to remove oxide scale mainly composed of Fe oxides. Figure 4 shows the condition after descaling treatment, and shows the welded material of Example 1 described later.
[0076] As shown in Figure 3, the surface of the weld metal in the welded area turned brown due to welding, and oxide scale consisting mainly of Fe oxide was confirmed. As shown in Figure 4, by carrying out appropriate descaling treatment, the oxide scale is removed and the metallic luster of the weld metal surface is restored.
[0077] To evaluate the relationship between the chemical composition of the weld metal surface and crevice corrosion resistance, welded materials made by butt-welding two sheets of duplex stainless steel were used. After descaling to remove oxide scale, the chemical composition of the weld metal surface was analyzed by XPS. In addition, after descaling to remove oxide scale, a crevice corrosion test was performed to evaluate crevice corrosion resistance.
[0078] The descaling method used to remove the oxide scale from the surface of the weld metal was either (1) pickling the surface of the weld metal, (2) electrolytic treatment of the surface of the weld metal in a neutral salt solution, or (3) reduction heat treatment of the surface of the weld metal. The circled lines in Figure 3 indicate the measurement positions in the XPS analysis.
[0079] Crevice corrosion resistance was evaluated by observing the maximum corrosion depth after immersing the welded material with a crevice in an adjustment liquid for three months. The adjustment liquid used was a 3.5% sodium chloride aqueous solution adjusted to pH 3.0 with hydrochloric acid at 45°C. If the maximum corrosion depth exceeded the critical crevice corrosion depth of 40 μm, it was evaluated as crevice corrosion having occurred ("X"). If the maximum corrosion depth did not exceed the critical crevice corrosion depth of 40 μm, it was evaluated as crevice corrosion not having occurred ("O").
[0080] Fig. 5 is a diagram showing a method for providing a gap to a welded material. Fig. 5A is a diagram showing a welded material in which materials to be welded are welded together. Fig. 5B is a diagram showing a state in which the surface of the welded metal is molded with an impression material. Fig. 5C is a diagram showing an operation of immersing the surface of the welded metal in an adjustment liquid. Fig. 5D is a diagram showing a state in which a gap is provided to the surface of the welded metal. In FIG. 5, reference numeral 4 denotes a welding material which is a material to be treated, reference numeral 6 denotes a weld metal, reference numeral 7 denotes an impression material, reference numeral 8 denotes a cable tie, and reference numeral 9 denotes an adjusting liquid.
[0081] As shown in Fig. 5A, a weld metal 6 is exposed on both sides of a welded material 4 formed by butt-welding two plates. Gaps were formed on the surfaces of the weld metal 6 exposed on both sides of the welded material 4 by using an impression material 7. The surface of the welded material 4 was left as received, and was only washed with acetone without being polished or passivated. A dental impression material made of vinyl silicone (manufactured by GC Corporation) was used as the impression material 7.
[0082] As shown in Fig. 5B, impression material 7 was pressed against both sides of weld metal 6 to form a mold of the surface of weld metal 6, and impression material 7 was once peeled off from weld material 4. The periphery of impression material 7 peeled off from weld material 4 was removed, and only a mold-forming portion of 20 mm in length × 20 mm in width was cut out. Then, as shown in Fig. 5C, an adjustment liquid was dropped on the surface of weld metal 6, and the molded impression material 7 was returned to its original position and molded.
[0083] 5D, fluororesin cable ties 8 were wrapped around the impression materials 7 on both sides of the welding material 4, and the impression materials 7 were fixed to the welding material 4. The welding material 4 with the gaps formed by the impression materials 7 was left in contact with the adjusting liquid for three months, and the erosion depth of the surface of the weld metal 6 was then observed.
[0084] Tables 1 and 2 show the degree of remaining oxide scale confirmed by visual inspection, the chemical composition of the weld metal surface measured by XPS analysis, the method of descaling to remove the oxide scale applied to the weld metal surface, and the evaluation results of crevice corrosion resistance. Table 1 shows the results when the welded material was S32750. Table 2 shows the results when the welded material was S32205.
[0085] [Table 1]
[0086] [Table 2]
[0087] The mass fraction of each element detected on the surface of the weld metal by XPS analysis is shown on the left side of the element column in Tables 1 and 2. The mass fraction is a value converted to a fraction per 100 mass% of the total of the metal elements contained in the weld metal, excluding oxygen and carbon contained in the weld metal.
[0088] In Tables 1 and 2, the mass ratio of each element detected on the surface of the weld metal to the base metal is shown on the right side of the element column. The mass fraction is a value obtained by dividing the amount of element detected on the surface of the weld metal [mass %] by the amount of element contained in the base metal [mass %]. For example, in the case of Cr in Example 1, the amount is 44 mass % on the surface of the weld metal and 25.73 mass % in the base metal, so the mass ratio is 44 / 25.73=1.71.
[0089] [Example 1] In Example 1, the surface of the weld metal of the welded material using S32750 was electrolytically treated in a solution of neutral salt. A 10% aqueous solution of sodium sulfate was used as the electrolyte. In the electrolyte at 30°C, a current density of 10 A / dm 2 The power was applied for five minutes.
[0090] In Example 1, the oxide scale was removed, and the metallic luster of the base was visible. The Cr content was 44.00 mass%, which was 1.71 times that of the base material. No Mn was detected. The Ni content was 3.45 mass%, which was 0.54 times that of the base material. The Mo content was 5.63 mass%, which was 1.65 times that of the base material. The crevice corrosion resistance was good. It is believed that the reason why no Mn was detected is because the oxide scale was sufficiently removed.
[0091] [Example 2] In Example 2, the surface of the weld metal of the welded material using S32750 was electrolytically treated in a solution of neutral salt. A 10% aqueous solution of ammonium sulfate was used as the electrolyte. In the electrolyte at 30°C, a current density of 10 A / dm 2 The power was applied for five minutes.
[0092] In Example 2, the oxide scale was removed, and the metallic luster of the base was visible. The Cr content was 46.50 mass%, which was 1.81 times that of the base material. No Mn was detected. The Ni content was 3.15 mass%, which was 0.49 times that of the base material. The Mo content was 5.63 mass%, which was 1.65 times that of the base material. The crevice corrosion resistance was good. It is believed that Mn was not detected because the oxide scale was sufficiently removed. Good results were obtained even when the components of the electrolyte were changed.
[0093] [Example 3] In Example 3, the surface of the weld metal of the welded material using S32750 was subjected to pickling treatment. The acid used was a hydrofluoric acid-nitric acid solution containing 20% nitric acid and 0.5% hydrofluoric acid. The welded material was immersed in the acid solution at 50° C. for 5 minutes.
[0094] In Example 3, the oxide scale was removed, and the metallic luster of the base was visible. The Cr content was 39.00 mass%, which was 1.52 times that of the base material. No Mn was detected. The Ni content was 3.25 mass%, which was 0.51 times that of the base material. The Mo content was 5.72 mass%, which was 1.67 times that of the base material. The crevice corrosion resistance was good. It is believed that the reason why no Mn was detected is because the oxide scale was sufficiently removed.
[0095] [Example 4] In Example 4, the surface of the weld metal of the welded material using S32750 was subjected to pickling treatment. The acid used was a hydrofluoric-nitric acid solution containing 10% nitric acid and 0.3% hydrofluoric acid. The welded material was immersed in the acid solution at 50° C. for 10 minutes.
[0096] In Example 4, the oxide scale was removed, and the metallic luster of the base was visible. The Cr content was 43.50 mass%, which was 1.69 times that of the base material. No Mn was detected. The Ni content was 3.65 mass%, which was 0.57 times that of the base material. The Mo content was 5.75 mass%, which was 1.68 times that of the base material. The crevice corrosion resistance was good. It is believed that the reason why Mn was not detected is that the oxide scale was sufficiently removed. Even if the acid concentration was reduced, good results were obtained by increasing the treatment time.
[0097] [Example 5] In Example 5, the surface of the weld metal of the weld material using S32750 was subjected to a reduction heat treatment. 10 -2 The sample was heat-treated at 400° C. for 2 hours under reduced pressure of Torr.
[0098] In Example 5, the oxide scale was removed, and the metallic luster of the base was visible. The Cr content was 39.60 mass%, which was 1.54 times that of the base material. No Mn was detected. The Ni content was 3.05 mass%, which was 0.48 times that of the base material. The Mo content was 5.33 mass%, which was 1.56 times that of the base material. The crevice corrosion resistance was good. It is believed that the reason why no Mn was detected is because the oxide scale was sufficiently removed.
[0099] [Example 6] In Example 6, the surface of the weld metal of the weld material using S32750 was subjected to a reduction heat treatment. 10 -4 The sample was heat-treated at 600° C. for 0.5 hours under reduced pressure of Torr.
[0100] In Example 6, the oxide scale was removed, and the metallic luster of the base was visible. The Cr content was 42.30 mass%, which was 1.64 times that of the base material. No Mn was detected. The Ni content was 3.23 mass%, which was 0.50 times that of the base material. The Mo content was 5.42 mass%, which was 1.59 times that of the base material. The crevice corrosion resistance was good. It is believed that the reason why Mn was not detected is because the oxide scale was sufficiently removed. Even if the treatment time was shortened, good corrosion resistance was obtained by increasing the degree of vacuum and temperature.
[0101] [Comparative Example 1] In Comparative Example 1, the surface of the weld metal of the weld material using S32750 was evaluated without removing the oxide scale.
[0102] In Comparative Example 1, the surface of the weld metal was brown, and metallic luster was not visible. The Cr content was 28.41 mass%, which was 1.10 times that of the base metal. The Mn content was 41.68 mass%, which was 83.4 times that of the base metal. Ni and Mo were not detected. The critical crevice corrosion depth was exceeded after immersion for three months, and the crevice corrosion resistance was poor. The reason why Ni and Mo were not detected is thought to be that the oxide scale was not removed and X-rays did not penetrate.
[0103] [Comparative Example 2] In Comparative Example 2, the surface of the weld metal of the welded material using S32750 was pickled. The acid used was 10% hydrochloric acid to which hexamethylenetetramine was added so that the concentration was 1.0%. The welded material was immersed in the acid solution at 30°C for 1 minute. Hexamethylenetetramine is a corrosion inhibitor added to general pickling solutions.
[0104] In Comparative Example 2, the degree of browning of the surface of the weld metal was reduced, but the metallic luster was not visible. The Cr content was 32.50 mass%, which was 1.26 times that of the base metal. No Mn, Ni, or Mo was detected. The crevice corrosion resistance was poor. This result indicates that in the case of pickling treatment with hydrochloric acid, oxide scale may not be sufficiently removed.
[0105] [Comparative Example 3] In Comparative Example 3, the surface of the weld metal of the welded material using S32750 was pickled. The acid used was a hydrofluoric nitric acid solution containing 10% nitric acid and 0.5% hydrofluoric acid. The welded material was immersed in the acid solution at 30°C for one minute. In Comparative Example 3, the hydrofluoric acid concentration, the temperature of the acid solution, and the pickling treatment time are milder than those in Example 4.
[0106] In Comparative Example 3, the oxide scale was removed and the metallic luster of the base was visible. The Cr content was 33.10 mass%, which was 1.29 times that of the base material. Mn, Ni, and Mo were not detected. The crevice corrosion resistance was poor. It is believed that Mn was not detected because the oxide scale was sufficiently removed. Although the oxide scale was removed from the outside, corrosion exceeding the critical crevice corrosion depth occurred. Since the Cr content was small and Ni and Mo were not detected, it is presumed that the oxide scale remains microscopically.
[0107] [Comparative Example 4] In Comparative Example 4, the surface of the weld metal of the welded material using S32750 was electrolytically treated in a neutral salt solution. A 10% aqueous solution of sodium sulfate was used as the electrolyte. The welded material was immersed in the electrolyte at 30° C. with a current density of 0.5 A / dm 2 The mixture was treated for 5 min.
[0108] In Comparative Example 4, the oxide scale was removed and the metallic luster of the base was visible. The Cr content was 26.30 mass%, which was 1.02 times that of the base material. Mn, Ni, and Mo were not detected. The crevice corrosion resistance was poor. It is believed that Mn was not detected because the oxide scale was sufficiently removed. Although the oxide scale was removed from the outside, corrosion occurred beyond the critical crevice corrosion depth. Since the Cr content was small and Ni and Mo were not detected, it is presumed that the oxide scale remains microscopically.
[0109] [Comparative Example 5] In Comparative Example 5, the surface of the weld metal of the welded material using S32750 was electrolytically treated in a solution of neutral salt. A 10% aqueous solution of sodium sulfate was used as the electrolyte. In the electrolyte at 30°C, a current density of 50 A / dm 2 In Comparative Example 5, the current density was higher than that in Example 1, and the current was passed for 5 minutes.
[0110] In Comparative Example 5, the oxide scale was removed and the metallic luster of the base was visible. The Cr content was 19.80 mass%, which was 0.77 times that of the base metal. No Mn was detected. The Ni content was 0.56 mass%, which was 0.09 times that of the base metal. The Mo content was 1.56 mass%, which was 0.46 times that of the base metal. The crevice corrosion resistance was poor. It is believed that the reason why no Mn was detected is that the oxide scale was removed. Although the oxide scale was removed from the outside, corrosion beyond the critical crevice corrosion depth occurred. It is presumed that this result was due to the current density being too high, which reduced the Cr, Ni, and Mo contents on the surface of the weld metal.
[0111] [Examples 1 to 6, Comparative Examples 1 to 5] In Examples 1 to 6 and Comparative Examples 1 to 5, the N content was larger than that of the base material. N is an austenite stabilizing element, and brings about effects such as improving corrosion resistance. However, no difference in the N content was confirmed regardless of the degree of removal of oxide scale.
[0112] [Example 7] In Example 7, the surface of the weld metal of the welded material using S32205 was electrolytically treated in a solution of neutral salt. The electrolyte used was a 10% aqueous solution of ammonium sulfate. In the electrolyte at 30°C, a current density of 10 A / dm 2 The power was applied for five minutes.
[0113] In Example 7, the oxide scale was removed, and the metallic luster of the base was visible. The Cr content was 33.22 mass%, which was 1.88 times that of the base material. No Mn was detected. The Ni content was 5.62 mass%, which was 0.46 times that of the base material. The Mo content was 5.63 mass%, which was 1.82 times that of the base material. The crevice corrosion resistance was good. It is believed that the reason why no Mn was detected is because the oxide scale was sufficiently removed.
[0114] [Example 8] In Example 8, the surface of the weld metal of the welded material using S32205 was electrolytically treated in a solution of neutral salt. The electrolyte used was a 10% aqueous solution of ammonium sulfate. In the electrolyte at 30°C, a current density of 10 A / dm 2 The power was applied for five minutes.
[0115] In Example 8, the oxide scale was removed, and the metallic luster of the base was visible. The Cr content was 34.26 mass%, which was 1.94 times that of the base material. No Mn was detected. The Ni content was 5.45 mass%, which was 0.45 times that of the base material. The Mo content was 5.23 mass%, which was 1.69 times that of the base material. The crevice corrosion resistance was good. It is believed that the reason why Mn was not detected is because the oxide scale was sufficiently removed. Good results were obtained even when the components of the electrolyte were changed.
[0116] [Example 9] In Example 9, the surface of the weld metal of the welded material using S32205 was subjected to pickling treatment. The acid used was a hydrofluoric acid-nitric acid solution containing 20% nitric acid and 0.5% hydrofluoric acid. The welded material was immersed in the acid solution at 50° C. for 5 minutes.
[0117] In Example 9, the oxide scale was removed, and the metallic luster of the base was visible. The Cr content was 32.99 mass%, which was 1.86 times that of the base material. No Mn was detected. The Ni content was 5.52 mass%, which was 0.46 times that of the base material. The Mo content was 5.46 mass%, which was 1.76 times that of the base material. The crevice corrosion resistance was good. It is believed that the reason why no Mn was detected is because the oxide scale was sufficiently removed.
[0118] [Example 10] In Example 10, the surface of the weld metal of the welded material using S32205 was subjected to pickling treatment. The acid used was a hydrofluoric-nitric acid solution containing 10% nitric acid and 0.3% hydrofluoric acid. The welded material was immersed in the acid solution at 50° C. for 10 minutes.
[0119] In Example 10, the oxide scale was removed, and the metallic luster of the base was visible. The Cr content was 36.21 mass%, which was 2.04 times that of the base material. No Mn was detected. The Ni content was 5.72 mass%, which was 0.47 times that of the base material. The Mo content was 5.82 mass%, which was 1.88 times that of the base material. The crevice corrosion resistance was good. It is believed that the reason why Mn was not detected is that the oxide scale was sufficiently removed. Even if the acid concentration was reduced, good results were obtained by increasing the treatment time.
[0120] [Example 11] In Example 11, the surface of the weld metal of the weld material using S32205 was subjected to a reducing heat treatment. 10 -2 The sample was heat-treated at 600° C. for 1 hour under reduced pressure of Torr.
[0121] In Example 11, the oxide scale was removed, and the metallic luster of the base was visible. The Cr content was 33.56 mass%, which was 1.90 times that of the base material. No Mn was detected. The Ni content was 5.66 mass%, which was 0.47 times that of the base material. The Mo content was 5.22 mass%, which was 1.68 times that of the base material. The crevice corrosion resistance was good. It is believed that the reason why no Mn was detected is because the oxide scale was sufficiently removed.
[0122] [Example 12] In Example 12, the surface of the weld metal of the weld material using S32205 was subjected to a reducing heat treatment. 10 -4 The sample was heat-treated at 400° C. for 1 hour under reduced pressure of Torr.
[0123] In Example 12, the oxide scale was removed, and the metallic luster of the base was visible. The Cr content was 34.23 mass%, which was 1.93 times that of the base material. No Mn was detected. The Ni content was 5.55 mass%, which was 0.46 times that of the base material. The Mo content was 5.31 mass%, which was 1.71 times that of the base material. The crevice corrosion resistance was good. It is believed that the reason why Mn was not detected is that the oxide scale was sufficiently removed. Even if the treatment time was shortened, good corrosion resistance was obtained by increasing the degree of vacuum and temperature.
[0124] [Comparative Example 6] In Comparative Example 6, the surface of the weld metal of the weld material using S32205 was evaluated without removing the oxide scale.
[0125] In Comparative Example 6, the surface of the weld metal was brown, and metallic luster was not visible. The Cr content was 20.14 mass%, which was 1.14 times that of the base metal. The Mn content was 28.42 mass%, which was 24.3 times that of the base metal. Ni and Mo were not detected. The critical crevice corrosion depth was exceeded after immersion for three months, and the crevice corrosion resistance was poor. The reason why Ni and Mo were not detected is thought to be that the oxide scale was not removed and X-rays did not penetrate.
[0126] [Comparative Example 7] In Comparative Example 7, the surface of the weld metal of the welded material using S32205 was pickled. The acid used was 10% hydrochloric acid with hexamethylenetetramine added to make the concentration 1.0%. The welded material was immersed in the acid solution at 30°C for 1 minute.
[0127] In Comparative Example 7, the degree of browning of the surface of the weld metal was reduced, but the metallic luster was not visible. The Cr content was 19.85 mass%, which was 1.12 times that of the base metal. No Mn, Ni, or Mo was detected. The crevice corrosion resistance was poor. This result indicates that in the case of pickling treatment with hydrochloric acid, oxide scale may not be sufficiently removed.
[0128] [Comparative Example 8] In Comparative Example 8, the surface of the weld metal of the welded material using S32205 was pickled. The acid used was a hydrofluoric nitric acid solution containing 10% nitric acid and 0.5% hydrofluoric acid. The welded material was immersed in the acid solution at 30°C for 1 minute. In Comparative Example 8, the hydrofluoric acid concentration, the temperature of the acid solution, and the pickling treatment time are milder than those in Example 10.
[0129] In Comparative Example 8, the oxide scale was removed and the metallic luster of the base was visible. The Cr content was 20.23 mass%, which was 1.14 times that of the base material. Mn, Ni, and Mo were not detected. The crevice corrosion resistance was poor. It is believed that Mn was not detected because the oxide scale was sufficiently removed. Although the oxide scale was removed from the outside, corrosion exceeding the critical crevice corrosion depth occurred. Since the Cr content was small and Ni and Mo were not detected, it is presumed that the oxide scale remains microscopically.
[0130] [Comparative Example 9] In Comparative Example 9, the surface of the weld metal of the welded material using S32205 was electrolytically treated in a solution of neutral salt. The electrolyte used was a 10% aqueous solution of sodium sulfate. The welded material was immersed in the electrolyte at 30° C. at a current density of 0.5 A / dm 2 The mixture was treated for 5 min.
[0131] In Comparative Example 9, the oxide scale was removed and the metallic luster of the base was visible. The Cr content was 18.85 mass%, which was 1.07 times that of the base material. Mn, Ni, and Mo were not detected. The crevice corrosion resistance was poor. It is believed that Mn was not detected because the oxide scale was sufficiently removed. Although the oxide scale was removed from the outside, corrosion occurred beyond the critical crevice corrosion depth. Since the Cr content was small and Ni and Mo were not detected, it is presumed that the oxide scale remains microscopically.
[0132] [Comparative Example 10] In Comparative Example 10, the surface of the weld metal of the welded material using S32205 was electrolytically treated in a neutral salt solution. A 10% aqueous solution of sodium sulfate was used as the electrolyte. In the electrolyte at 30°C, a current density of 50 A / dm 2 In Comparative Example 5, the current density was higher than that in Example 7.
[0133] In Comparative Example 10, the oxide scale was removed and the metallic luster of the base was visible. The Cr content was 14.80 mass%, which was 0.84 times that of the base metal. No Mn was detected. The Ni content was 0.42 mass%, which was 0.03 times that of the base metal. The Mo content was 1.88 mass%, which was 0.61 times that of the base metal. The crevice corrosion resistance was poor. It is believed that the reason why no Mn was detected is that the oxide scale was removed. Although the oxide scale was removed from the outside, corrosion beyond the critical crevice corrosion depth occurred. It is presumed that this result was due to the current density being too high, which reduced the Cr, Ni, and Mo contents on the surface of the weld metal.
[0134] [Examples 7 to 12, Comparative Examples 6 to 10] In Examples 7 to 12 and Comparative Examples 6 to 10, the N content was larger than that of the base material. N is an austenite stabilizing element, and has the effect of improving corrosion resistance, etc. However, no difference in the N content was confirmed regardless of the degree of oxide scale removal. [Explanation of symbols]
[0135] 1 electrolytic cell 2 Electrolyte 3 electrodes 4. Materials to be treated (welded structures, welded materials) 5 DC power supply 6 Welding metal 7 Impression material 8 Cable ties 9 Adjustment liquid
Claims
1. A welded structure in which duplex stainless steel is welded, The welded structure has a welded portion in which a base material formed of duplex stainless steel is joined via a weld metal, A welded structure, wherein the amount of Cr at a surface of the weld metal measured by X-ray photoelectron spectroscopy is 1.5 times or more the amount of Cr in the base metal, in mass % excluding oxygen and carbon.
2. 2. The welded structure of claim 1, A welded structure, wherein an amount of Ni at a surface of the weld metal measured by X-ray photoelectron spectroscopy is 0.4 times or more of an amount of Ni in the base metal, and an amount of Mo at a surface of the weld metal measured by X-ray photoelectron spectroscopy is 1.5 times or more of an amount of Mo in the base metal, in mass % excluding oxygen and carbon.
3. 3. The welded structure of claim 2, A welded structure, wherein the amount of Mn at a surface of the weld metal measured by X-ray photoelectron spectroscopy is equal to or less than the amount of Mn in the base metal, in mass % excluding oxygen and carbon.
4. 2. The welded structure of claim 1, A welded structure in which the weld metal has had oxide scale removed from its surface.
5. 2. The welded structure of claim 1, The weld metal is a welded structure formed by integrating the base material, the mating material, and a filler metal.
6. A method for finishing a welded structure in which duplex stainless steel is welded, comprising the steps of: The process includes removing oxide scale from a welded portion where a base material formed of duplex stainless steel is joined via a weld metal, The method for finishing a welded structure, wherein the step of removing the oxide scale is a step of removing oxide scale containing Fe from a surface of the weld metal such that an amount of Cr on the surface of the weld metal, as measured by X-ray photoelectron spectroscopy, is 1.5 times or more the amount of Cr in the base metal, in mass % excluding oxygen and carbon.
7. A method for finishing a welded structure according to claim 6, comprising the steps of: The step of removing the oxide scale is a step of removing oxide scale containing Fe from a surface of the weld metal such that an amount of Ni on the surface of the weld metal measured by X-ray photoelectron spectroscopy is 0.4 times or more the amount of Ni in the base metal, and an amount of Mo on the surface of the weld metal measured by X-ray photoelectron spectroscopy is 1.5 times or more the amount of Mo in the base metal, in mass % excluding oxygen and carbon.
8. A method for finishing a welded structure according to claim 6, comprising the steps of: The method for finishing a welded structure, wherein the step of removing the oxide scale is a step of removing oxide scale containing Fe from a surface of the weld metal such that an amount of Mn on the surface of the weld metal measured by X-ray photoelectron spectroscopy is equal to or less than an amount of Mn in the base metal, in mass % excluding oxygen and carbon.
9. A method for finishing a welded structure according to claim 6, comprising the steps of: The step of removing the oxide scale is a step of subjecting the surface of the weld metal to an acid pickling treatment with nitric acid, sulfuric acid, hydrofluoric acid, or a mixed acid of at least one of these.
10. A method for finishing a welded structure according to claim 6, comprising the steps of: The step of removing the oxide scale is a step of pickling the surface of the weld metal with nitric acid of 2% or more and 50% or less, sulfuric acid of 2% or more and 50% or less, or hydrofluoric acid-nitric acid mixture of nitric acid of 2% or more and 50% or less and hydrofluoric acid of 0.2% or more and 10% or less.
11. A method for finishing a welded structure according to claim 6, comprising the steps of: The method for finishing a welded structure, wherein the step of removing the oxide scale comprises subjecting the surface of the weld metal to an electrolytic treatment in a neutral salt solution.
12. A method for finishing a welded structure according to claim 11, comprising the steps of: The method for finishing a welded structure, wherein the neutral salt is sodium sulfate, sodium nitrate, or ammonium sulfate.
13. A method for finishing a welded structure according to claim 11, comprising the steps of: The current density of the weld metal in the electrolytic treatment is 2 A / dm 2 20A / dm or more 2 A method for finishing a welded structure comprising:
14. A method for finishing a welded structure according to claim 6, comprising the steps of: The method for finishing a welded structure, wherein the step of removing the oxide scale comprises heat treating the surface of the weld metal in a reduced pressure atmosphere.
15. A method for finishing a welded structure according to claim 6, comprising the steps of: The step of removing the oxide scale comprises heat treating the surface of the weld metal in a reduced pressure atmosphere of 10 −2 Torr or less at 400° C. or more for one hour or more.
Citation Information
Patent Citations
FERRITIC AUSTENITIC STAINLESS STEEL AND ITS USE
DE69421281D1
Method for modifying stainless steel weld zone
JP1997013124A
Acid cleaning method for metal surface, acid cleaning solution thereof, and method for regenerating cleaning waste solution
JP1998510593A
Build-up welding material and build-up clad material
JP1999226778A
Pickling agent for dual-phase stainless steel and method for pickling the same therewith
JP2007297697A